ANALISIS STRATEGI PEMASARAN YANG EFEKTIF UNTUK MENINGKATKAN MUTU PENJUALAN PADA PRODUK KOSMETIK DI ERA DIGITAL ANALYSIS OF EFFECTIVE MARKETING STRATEGIES TO IMPROVE SALES QUALITY OF COSMETIC PRODUCTS IN THE DIGITAL ERA - Agustina, Renita; Fasa, Muhammad Iqbal (STAI Darul Qalam Tangerang, 2024)
This study aims to analyze effective digital marketing strategies in improving the quality of cosmetic product sales in the digital era. With the rapid development of technology, digital marketing has become an important instrument for cosmetic companies to reach consumers more widely without geographical limitations. This study uses a qualitative approach with a descriptive type to examine the implementation of various digital strategies such as social media, influencer marketing, interactive content, and email marketing in an effort to increase sales. The results of the study show that the right digital marketing strategy can significantly increase brand awareness, competitiveness, and the quality of cosmetic product sales. Digitalization of marketing also helps companies build stronger relationships with consumers through more personal and targeted interactions.